On thinking statistically : a short introduction - Brodie, M. B. (Morris Bernard) (London : Heinamann, 1972)
This text is intended for a wide range of busy people in all walks of life - in business, commerce , the public service.
includes note for further readings
includes index
ijb, 15/01/2019
Loans
Keywords: Statistics